Effect of Leukocyte- and Platelet-Rich Fibrin in Postoperative Recovery Following Impacted Mandibular Third Molar Surgery: A Split Mouth Study - dos Santos, Mateus Veppo; Monteiro, Carolina Brito; Goulart, Douglas Rangel; Aguiar Silva, Isabella Vieira; de Souza, Kevin Caio Ferreira; Vieira Frujeri, Maria de Lourdes; Matias, Micaele da Silva (The Journal of Dentists, 2023)
Objective: The surgeries for extraction of impacted lower third molars are more associated with complications such as pain and postoperative edema. The purpose of the present study was to evaluate the impact of the use of Leukocyte- and Platelet-Rich Fibrin (L-PRF) on pain and edema after extraction of impacted mandibular third molars. Material and Methods: A cross-sectional split-mouth study was conducted with 15 volunteer patients who had both impacted mandibular third molars with indication for extraction. The removal surgery was performed one side at a time, with an interval of 14 days. One side received L-PRF while the other did not. Patients were evaluated on the 2nd and 7th postoperative days for mouth opening, pain and edema. Results: In total, data from 14 patients (4 men and 10 women), with a mean age of 21.83 ± 2.8 years were evaluated. There was no statistically significant difference regarding mouth opening, pain and edema on the 7th postoperative day. On the second postoperative day, greater edema was observed in the control group with a statistically significant difference (p = 0.01). Conclusions: Under controlled conditions, the L-PRF does not appear to alter postoperative recovery after extraction of the lower third molars in terms of pain, edema and the ability to open the mouth. Despite the statistically significant difference in edema on the second day, the means were very close and were not clinically relevant.